PENGARUH KEPUASAN BELAJAR TERHADAP ENGAGEMENT AKADEMIK MAHASISWA PADA PERKULIAHAN SISTEM HYBRID - Mohammad, Wily; Ayunda Rahmawati, Dayyinah (CV. AKIRA JAVA BULU, 2025)
This research aims to examine the effect of learning satisfaction on students' academic engagement in the context of hybrid lectures in Indonesia. The research method used is quantitative with a survey approach, involving 55 students from various universities in Indonesia who filled out questionnaires via Google Form. The data were analyzed using simple regression techniques to see the relationship between learning satisfaction and academic engagement. The results of the analysis show that learning satisfaction does not have a significant effect on students' academic engagement. This finding indicates that students' academic engagement in hybrid lectures is influenced by factors other than learning satisfaction. This study recommends that further research consider other variables such as learning motivation, learning effectiveness, and social support to understand academic engagement more comprehensively.